ANALISIS MANAJEMEN KELAS PADA PEMBELAJARAN DI KELOMPOK B TAMAN KANAK-KANAK SUSTER PONTIANAK - Sumiati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractClassroom management is a conscious effort to plan, organize, actualize and to control or supervision of the programs and activities in the classroom so that the learning process can take place in a systematic, effective, and efficient, so all of the potential that learners have can be optimized. The method used in this research is descriptive and using qualitative research approach. The technique used in this research is interview, observation and documentation. Subjects in this study are four classroom teachers of group B Suster Kindergarten Pontianak. From the results of the research and discussion of this study, it can be concluded that 1) In planning the classroom management, the teacher has prepared the classroom well enough, neat and clean. 2) In organizing the classroom the teacher is doing well enough, the teacher has formed a child seat group. 3) When the teachers do the implementation of classroom management is well enough, the teachers interact with all of the children, so the children will be active in following the learning process in the classroom.4) In conducting supervision of classroom management, the teacher has done well enough, because the researcher watches the teacher to supervise each learner. 5) The problem faced was because of the absence of companion teachers who help and lack of learning media.Keywords:Classroom Management, Learning